Buttevant, County Cork, Ireland - Rae, Edwin (My University, 2007)
Abbey mistakenly identified by Rae as Franciscan [RM]
(handwritten on back of image): 72.241. Buttevant (Cork) Franciscan friary. Enfeu (tomb niche) built into E. wall of transept chapel and capitals at S. end. (multiple images on file)
Keywords: Church architecture Ireland Cork.; Church buildings; Stone buildings; Augustinian architecture; Arches; Late Medieval